1971
DOI: 10.1139/p71-380
|View full text |Cite
|
Sign up to set email alerts
|

Induced Fundamental Infrared Band of Nitrogen Dissolved in Solid Argon

Abstract: The induced fundamental infrared band of nitrogen dissolved in solid argon was studied over the temperature range 55–81 K with a path length of 40 cm and molar N2 concentrations of 1−2%. The spectrum consists of combination tones of lattice transitions with the N2 1 ← 0 vibrational transition. Lattice transition frequencies of 70 and 39 cm−1 at 55 K are identified with a local mode and vibrations of the host-lattice atoms respectively. We have computed the local-mode frequency over the experimental temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1972
1972
1984
1984

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…This work has been extended to D, in solid argon and H, in solid krypton by De Remigis and Welsh (1970), the results confirming the original interpretation. Due to the relatively high temperatures, 80 K for the Ar host and 11 5 K for the Kr host, both the sum and difference bands appear.…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…This work has been extended to D, in solid argon and H, in solid krypton by De Remigis and Welsh (1970), the results confirming the original interpretation. Due to the relatively high temperatures, 80 K for the Ar host and 11 5 K for the Kr host, both the sum and difference bands appear.…”
Section: Introductionsupporting
confidence: 71%
“…Unfortunately values of Kj cannot be determined directly from the experimental spectra (Kriegler and Welsh 1968;De Remigis and Welsh 1970) which, due to the overlapping of the various spectral features only give a<o> = C a j(o) j whereas it is the Aj(o), defined in [20] which appear in eq. 25.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lattice spectrum obtained by De Remigis et al [25] for the XJAr system was found, depending on the temperature of the system, to result from a local mode a t 63 to 70 cm-1 and an inband contribution a t 30 to 40 cm-1 associated with the transverse region of the Ar phonon density of states. For the H,/Ar system [23] and DJAr system [24] large lattice distortions about the molecular impurity required an 'effective lattice' [26] approach to explain the features of the sideband (i.e.…”
Section: Introductionmentioning
confidence: 89%
“…However, if there are two 0, molecules in this defect space, we make the following approximation: that one 0, is at S ( and the other is averaged, with equal probability, over the twelve nearest neighbour positions. Thus the change of dynamical matrix V t is We used the method described in [25], which includes temperature corrections, to obtain P and the AW. The various force constant changes are given in Table 3.…”
Section: ( { R ( T ) } )mentioning
confidence: 99%